Diagnostic and Therapeutic Challenges of Hereditary Tyrosinemia Type 1 in Lebanon: A 12-Year Retrospective Review - Daou, Karim N.; Barhoumi, Abir; Bassyouni, Amina; Karam, Pascale E. (Frontiers in Pediatrics, 2021)
Abstract Background: Hereditary tyrosinemia type 1 is a rare genetic disorder leading to liver cirrhosis and hepatocellular carcinoma. Few decades ago, dietary measures and ultimately liver transplant constituted the only treatment modalities. Nowadays, early diagnosis and therapy with nitisinone can reverse the clinical picture. In developing countries, diagnostic and therapeutic challenges may affect the outcome of this disease. The choice of the treatment modality may depend on the economic status of each country. Few reports on the long-term outcome of hereditary tyrosinemia type 1 are available from developing and Arab countries. Methods: A retrospective study of charts of Lebanese patients diagnosed with tyrosinemia type 1 and followed, at the American University of Beirut, during a 12-year period was performed. Clinical presentation and liver biochemical profile at diagnosis were analyzed, along with therapeutic modalities and long-term outcome. Results: Twenty-two children were diagnosed and followed during the study period. Median age at diagnosis was 7 months (range: one day to 35 months). Most of the patients presented with hepatomegaly and jaundice. Four patients were referred for atypical presentations with developmental delay and seizures, secondary to undiagnosed hypoglycemia episodes. Around half of the patients presented with failure to thrive. Transaminitis, cholestasis and increased α-fetoprotein level were variably present at diagnosis (36% to 50%). All patients had elevated plasma tyrosine and urinary succinylacetone levels. Genetic testing was performed in 9%. Only one third could be treated with nitisinone. Liver transplant was electively performed in 9% of cases, to overcome the long-term cost of nitisinone. One third of the patients died between the age of 1 month and 11 years. Surviving patients are still candidates for liver transplant. Conclusion: Our experience reflects the challenges of diagnosis and treatment of hereditary tyrosinemia type 1 in a developing country. In the absence of specific neonatal screening, early diagnosis relies mostly on the clinical awareness of the physician. Long-term nitisinone use may be deterred by its high cost and liver transplantation carries risks of surgical complications. New, effective, and less expensive treatments are needed, especially for developing countries.